Robotic versus laparoscopic gastrectomy for gastric cancer: a systematic review and meta-analysis - Ma, Jianglei (World J Surg Oncol, 2020)
BACKGROUND: To date, robotic surgery has been widely used worldwide. We conducted a systematic review and meta-analysis to evaluate short-term and long-term outcomes of robotic gastrectomy (RG) in gastric cancer patients to determine whether RG can replace laparoscopic gastrectomy (LG). METHODS: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was applied to perform the study. Pubmed, Cochrane Library, WanFang, China National Knowledge Infrastructure (CNKI), and VIP databases were comprehensively searched for studies published before May 2020 that compared RG with LG. Next, two independent reviewers conducted literature screening and data extraction. The quality of the literature was assessed using the Newcastle-Ottawa Scale (NOS), and the data analyzed using the Review Manager 5.3 software. Random effects or fixed effects models were applied according to heterogeneity. RESULTS: A total of 19 studies including 7275 patients were included in the meta-analyses, of which 4598 patients were in the LG group and 2677 in the RG group. Compared with LG, RG was associated with longer operative time (WMD = −32.96, 95% CI −42.08 ~ −23.84, P < 0.001), less blood loss (WMD = 28.66, 95% CI 18.59 ~ 38.73, P < 0.001), and shorter time to first flatus (WMD = 0.16 95% CI 0.06 ~ 0.27, P = 0.003). There was no significant difference between RG and LG in terms of the hospital stay (WMD = 0.23, 95% CI −0.53 ~ 0.98, P = 0.560), overall postoperative complication (OR = 1.07, 95% CI 0.91 ~ 1.25, P = 0.430), mortality (OR = 0.67, 95% CI 0.24 ~ 1.90, P = 0.450), the number of harvested lymph nodes (WMD = −0.96, 95% CI −2.12 ~ 0.20, P = 0.100), proximal resection margin (WMD = −0.10, 95% CI −0.29 ~ 0.09, P = 0.300), and distal resection margin (WMD = 0.15, 95% CI −0.21 ~ 0.52, P = 0.410). No significant differences were found between the two treatments in overall survival (OS) (HR = 0.95, 95% CI 0.76 ~ 1.18, P = 0.640), recurrence-free survival (RFS) (HR = 0.91, 95% CI 0.69 ~ 1.21, P = 0.530), and recurrence rate (OR = 0.90, 95% CI 0.67 ~ 1.21, P = 0.500). CONCLUSIONS: The results of this study suggested that RG is as acceptable as LG in terms of short-term and long-term outcomes. RG can be performed as effectively and safely as LG. Moreover, more randomized controlled trials comparing the two techniques with rigorous study designs are still essential to evaluate the value of the robotic surgery for gastric cancer. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12957-020-02080-7.